ASSESSMENT OF BASIN YIELD FOR THE WESTERN GHAT RIVERS OF KERALA - C.G. Madhusoodhanan; M.R.Y. Putty; T.I. Eldho (Hydro 2011, 2012)
Assessment of basin yield for a river basin is vital in the planning and management of its water resources. In the absence of gauged data, various empirical methods are used to derive the basin yield in most of the rivers in India and Kerala is not an exception. The present study examines the applicability of various empirical methods to find out the basin yield that are commonly used in the country, in estimating the water yield of the Western Ghats rivers of Kerala. It was found that the empirical methods currently in use are incapable of an accurate assessment of the basin yield in the Western Ghat rivers of Kerala.